2023
DOI: 10.1093/ofid/ofad047
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Long COVID Symptoms in an Online Cohort Study

Abstract: Background Few prospective studies of Long COVID risk factors have been conducted. The purpose of this study was to determine whether sociodemographic factors, lifestyle, or medical history preceding COVID-19 or characteristics of acute SARS-CoV-2 infection are associated with Long COVID. Methods The COVID-19 Citizen Science (CCS) study is an online cohort study that began enrolling March 26, 2020, with longitudinal assessmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 34 publications
(41 reference statements)
7
44
0
Order By: Relevance
“…Investigation into mechanisms of PASC may benefit from proof-of-concept approaches to identify potential therapies. Although vaccination reduces the risk of PASC [57,58] and the newer circulating variants may be associated with lower risk of Long COVID [59], there is no data regarding whether anti-viral, anti-inflammatory, or anti-coagulant strategies improve exercise capacity in PASC. In chronotropic incompetence separate from COVID-19, chronic supervised exercise is the only intervention demonstrated to improve exercise capacity and surrogates of autonomic function [60][61][62].…”
Section: Implications For Therapymentioning
confidence: 99%
“…Investigation into mechanisms of PASC may benefit from proof-of-concept approaches to identify potential therapies. Although vaccination reduces the risk of PASC [57,58] and the newer circulating variants may be associated with lower risk of Long COVID [59], there is no data regarding whether anti-viral, anti-inflammatory, or anti-coagulant strategies improve exercise capacity in PASC. In chronotropic incompetence separate from COVID-19, chronic supervised exercise is the only intervention demonstrated to improve exercise capacity and surrogates of autonomic function [60][61][62].…”
Section: Implications For Therapymentioning
confidence: 99%
“…Others have demonstrated faster viral clearance with nirmatrelvir/ritonavir [24, 25]; as higher viral loads and prolonged viral shedding have been previously associated with risk of Long COVID [3, 4], there is a strong rationale for the hypothesis that treatment with nirmatrelvir/ritonavir may lower the risk of Long COVID. Secondly, in this cohort, we have previously shown that the number of symptoms during acute infection is associated with Long COVID symptoms independent of vaccination and variant wave [15], but whether reducing acute symptoms with antiviral therapy reduces risk of Long COVID has not been demonstrated.…”
Section: Discussionmentioning
confidence: 93%
“…The primary outcome was ≥1 self-reported Long COVID symptom more than 90 days after first SARS-CoV-2 positive test on a cross-sectional survey distributed in November 2022 that asked about presence, duration, and severity of Long COVID symptoms using a non-validated instrument as we have previously published [15]. Symptoms queried included fatigue, shortness of breath, confusion, headache, altered taste and smell, joint pain, muscle aches, cough, chest pain, scratchy throat, nausea, vomiting, diarrhea, fever, chills, red or painful eyes, sore throat, and other.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through impacting physical and mental functioning (3), long COVID can contribute to mental health disorders including anxiety and depression (4). Yet only a handful of US population-based studies have explored sociodemographic and socioeconomic predictors of long COVID and economic and health sequelae, and such studies remain limited to relatively small samples (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%